Efficient Design of Drip Irrigation System using Water and Fertilizer Application Uniformity at Different Operating Pressures in a Semi‐Arid Region of India†. (13th February 2017) - Kumar, Mukesh; Kumar, Rohitashw; Rajput, T.B.S.; Patel, Neelam
Abstract: Performance evaluation of irrigation has been an important area of research for better management of water resources. The present study was conducted to evaluate the effect of drip lateral lengths and system operating pressures on water and fertilizer application uniformity at the Indian Agricultural Research Institute (IARI), New Delhi, India. The following parameters of nutrients and water were studied to design and evaluate the performance of drip irrigation systems: (i) uniformity coefficient; (ii) discharge variation; (iii) distribution uniformity; (iv) statistical uniformity. Drip‐line lengths and system operating pressures ( P  < 0.05 and P  < 0.01) significantly affect the different parameters of fertilizer and water application. The highest values of uniformity coefficient (99.2%), statistical uniformity (99.2%) and distribution uniformity (97.4%) for irrigation water were observed at a pressure of 1.5 kg cm −2 with a 25 m long drip‐line. Lower values of discharge variation (2.65%) and coefficient of variation (0.04) were observed at the same operating pressure (1.5 kg cm −2 ) and drip‐line length. However, the lowest value of the uniformity coefficient (88.1%), statistical uniformity (93.7%) and distribution uniformity (93.2%) for irrigation water were recorded at 0.5 kg cm −2 pressure with a 100 m long drip‐line length. The highest values of urea, potassium and phosphorus distribution uniformity were found to be 97.8, 97.1 and 98.2%, respectively, at 1.5 kg cm −2 pressure with 25 m long drip‐line, and lower values of urea, potassium and phosphorus distribution uniformity (93.1, 92.6 and 93.2%, respectively) were recorded at 0.5 kg cm −2 pressure with a 100 m long drip‐line. Water and fertilizer distribution uniformity decreased with increase in drip‐line length, and increased with increase in system operating pressure. Copyright © 2017 John Wiley & Sons, Ltd.